PERLINDUNGAN HUKUM BAGI PENGHADAP (WNA) ATAS AKTA PERJANJIAN PINJAM NAMA YANG DINYATAKAN BATAL - Rahaldy Briwijaya (JURNAL ILMIAH NUSANTARA, 2024)
Nominee agreement are often used as a vehicle to smuggle the law. As in a decision in Bali, the parties used a name loan agreement for a foreign national to own land in Indonesia. The agreement was made authentically before a Notary. There are two problem formulations; first, how is the legal protection for the confronter of a null and void name loan agreement? Second, how is the responsibility of the Notary for the cancellation of the deed he made? This research uses normative research. The research approach uses statutory and conceptual approaches. The data analysis used is qualitative analysis. The results of the study show that the legal protection for the confronter of the name borrowing agreement that is null and void is by requesting compensation to the Notary as described in Article 51 paragraph (4) of Law Number 2 of 2014 concerning Amendments to Law Number 30 of 2004 concerning Notary Position. Notary accountability is inherent from the time the oath is taken until the end of the notary's life. In carrying out his/her position, a notary must comply with regulations such as the UUJN, the Notary Code of Ethics, and other relevant regulations. In making an authentic deed, a notary is authorized over every deed he makes. If there is an error or negligence that results in the cancellation of the deed, the notary can be held accountable either administratively, civilly or criminally. All three sanctions can be imposed on the Notary in accordance with the procedures and regulations that govern.